Management of a patient with familial idiopathic pulmonary fibrosis - Böing, S.; George, S.; Hagmeyer, L. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF), the most common subtype of idiopathic interstitial pneumonia, is a chronic progressive lung disease with a very high mortality. Usually diagnosis is established in adults older than 50 years and most cases are considered to be sporadic. Individuals with a familial form of IPF have at least one affected member in the same primary biological family and account for less than 5% of total patients. Sporadic and familial IPF are clinically and histologically indistinguishable from one another, although some familial forms appear to develop at an earlier age and exhibit different patterns of gene transcription. This case study describes the early clinical course of a patient diagnosed with a familial form of IPF.